European multicentre double-blind placebo-controlled trial of Nilvadipine in mild-to-moderate Alzheimer's disease—the substudy protocols: NILVAD frailty; NILVAD blood and genetic biomarkers; NILVAD cerebrospinal fluid biomarkers; NILVAD cerebral blood flow. Issue 7 (19th July 2016) - Meulenbroek, Olga; O'Dwyer, Sarah; de Jong, Daan; van Spijker, Gerrita; Kennelly, Sean; Cregg, Fiona; Olde Rikkert, Marcel; Abdullah, Laila; Wallin, Anders; Walsh, Cathal; Coen, Robert; Kenny, Rose Anne; et al.
Abstract : Introduction: In conjunction with the NILVAD trial, a European Multicentre Double-Blind Placebo Controlled trial of Nilvadipine in Mild-to-Moderate Alzheimer's disease (AD), there are four NILVAD substudies in which eligible NILVAD patients are also invited to participate. The main NILVAD protocol was previously published in BMJ Open (2014). The objectives of the NILVAD substudies are to determine whether frailty, cerebrospinal fluid (CSF), blood biomarker profile and Apolipoprotein E (APOE) status predict response to Nilvadipine, and to investigate the effect of Nilvadipine on cerebral blood flow and blood biomarkers. Methods and analysis: All participants who fulfil criteria for the main NILVAD study are eligible for participation in the NILVAD substudies. Participation is subject to informed consent and whether the substudy is available at a particular NILVAD study site. Each substudy entails extra measurements during the course of the main NILVAD study. For example, in the blood and genetic biomarkers substudy, extra blood (30 mL) will be collected at week 0, week 13, week 52 and week 78, while in the cerebral blood flow substudy, participants will receive an MRI and transcranial Doppler measurements at week 0, week 26 and week 78. In the CSF substudy, 10 mL CSF is collected at week 0 and week 78. Ethics and dissemination: All NILVAD substudies and all subsequent amendments have received ethical approval within each participating country, according to national regulations. Each participant provides written consent to participate. All participants remain anonymised throughout and the results of each substudy will be published in an international peer reviewed journal. Trial registration number: EUDRACT 2012-002764-27; Pre-results.